Understanding Representation - Webb, Jen (Understanding contemporary culture series, 2009)
Understanding Representation offers an accessible, engaging, and genuinely interdisciplinary introduction to the concept of representation. Drawing together the ideas, practices, and techniques associated with the subject, this book puts them in historical context and demonstrates their relevance to everyday life. Topics include linguistic and political representation, art and media, and philosophical and cognitive approaches.